Assessment System of Master’s Level at Tribhuvan University: A Review - Khanal, Ganesh Prasad; Timilsena, Narayan Prasad (Innovative Research Journal, 2025)
The assessment system at the master's level at Tribhuvan University (TU) has undergone significant reforms, particularly in its grading and evaluation methods. The university follows a semester-based and annual-based assessment structure, with internal evaluations, practical assessments, and final examinations contributing to students' overall grades. This paper reviews the examination policies, grading system, evaluation criteria, and recent changes implemented by TU to enhance academic quality. The study highlights the current assessment system's strengths and challenges and suggests areas for improvement.